Effects of Pentoxifylline in a Rat Model of Manganism: Evaluation of the Possible Toxicity. (20th September 2021) - Tanideh, Romina; Farshad, Omid; Jamshidzadeh, Akram; Iraji, Aida
Abstract : Objective . Manganese (Mn) has been reported, through dietary and occupational overexposure, to induce neurotoxicity named manganism. Pentoxifylline (PTX) administration attracts much attention considering the beneficial properties of PTX, as an anti-inflammatory and smooth muscle relaxation agent. This in vivo study aims to evaluate the effect of PTX on manganism in rat model. Materials and Methods . Thirty adult male Sprague Dawley rats received MnCl2 (100 mg/kg, i.p. on days 1, 3, and 7) during a week alone or in combination with PTX (300 mg/kg, i.p. every day for 8 consecutive days on manganism rat model). Several locomotor activity indices, as well as biomarkers of oxidative stress, were monitored in the brain tissue of Mn-exposed animals. Results . It was found that PTX supplementation (300 mg/kg, i.p.) deteriorated the Mn-induced locomotor deficit. This drug also increased the Mn brain accumulation as well as reactive oxygen species (ROS) and lipid peroxidation products in the manganism rat model. Moreover, the levels of total antioxidant capacity (TAC) and glutathione (GSH) were shown to be reduced significantly compared to the control group. Conclusion . The results of this study revealed that PTX at a high dose (300 mg/kg) might increase manganism complications. PTX lowers the blood viscosity, improves the tissue perfusion, and increases the Mn levels in the brain.